Mummucina huaripampae sp. nov. (Solifugae: Mummuciidae), a new solifuge species from the Peruvian Central Andes - Cossios, Daniel (2023)
A new species of Mummuciidae, Mummucina huaripampae sp. nov., from Huaripampa, between 3352 and 3568 m a.s.l. in the department of Junín, central Peru, is described and illustrated. This is the first Mummucina species registered for Junín, and the fourth for Peru. With this description, the number of known Mummucina species rises to seven.